EVALUASI KERUSAKAN JEMBATAN MENGGUNAKAN METODE BRIDGE MANAGEMENT SYSTEM (BMS)( Studi Kasus: Jembatan Bengkalis) - Simanjuntak, Benget Rio Sanses; M. Gala Garcya; Galih Sandi Tias (Jurnal TeKLA: Jurnal Inovtek Seri Teknik Sipil dan Aplikasi, 2024)
Bridges play a significant position in the route network system because of the significant consequences if the bridge is damaged or does not play a role properly. Bridges also play a vital role in infrastructure, supporting economic, social, and cultural activities to achieve balanced and equitable development. However, a bridge can be at risk if it is not designed in accordance with the use of the class of path it follows, so that it can affect traffic safety, so it is necessary to try the name of bridge condition monitoring. Bridge condition monitoring is attempted using the Bridge Management System (BMS) procedure, which is designed to control, conduct, and monitor bridges. Bridge checks are tried carefully, listed evaluating the detailed state of each damaged element, so that a state value is obtained. State evaluation using the BMS procedure, each damage is categorized into 5 levels, with level 1 being the lowest and level 5 being the highest. In this research, the author conducted an evaluation of the condition of the Bengkalis Bridge. Based on the results of the research, it was found that the NK of the bridge is 3, so it requires immediate attention because it is likely to become serious within the next 12 months. It is hoped that the results of this study can share guidelines for improving the expertise and performance of the Bengkalis Bridge. Based on the evaluation results, the Bengkalis Bridge is categorized as severely damaged with a value of 3 and has an age of 42 years.